Is white the new blue? The impact on gender wage and employment differentials of offshoring of white-collar jobs in the United States - Ebru Kongar; Mark Price (The University of Utah, Department of Economics, 2007)
Since the mid-1990s, offshore production has become increasingly important in white-collar, service sector activities in the U.S. economy. This development coincided with a stagnant gender wage gap over this period. This paper categorizes white-collar service sector occupations into two groups based on whether or not an occupation is at risk of being offshored and assesses the relative contribution of these two groupings, through their employment and wages, to the stagnation of the gender wage gap between 1995 and 2005. Applying standard decomposition methods to Current Population Survey and Displaced Workers Survey data shows that in at-risk occupations, low-wage women's employment declined, leading to an artificial increase in the average wage of remaining women thereby narrowing the gender wage gap. This improvement in the gender wage gap was offset by the relative growth of high-wage male employment in atrisk occupations and the widening of the gender wage gap within not-at-risk occupations.
Keywords: 330